Microwave pyrolysis of biomass within a liquid medium - Shepherd, B.J.; Ryan, J.; Adam, M.; Beneroso Vallejo, D.; Castaño, P.; Kostas, E.T.; Robinson, J.P. (Elsevier, 2018)
A new approach to pyrolysis is demonstrated that uses microwave heating combined with an external liquid media at atmospheric pressure. The liquid acts as the inerting medium instead of the traditional inert gas, and also acts as a heat-sink to maintain the external temperature at the normal boiling point of the liquid. The ability to regulate the external temperature using a liquid offers significant advantages over established pyrolysis technologies and is only possible due to the selective and volumetric heating that occurs with microwaves. The new concept overcomes many of the challenges encountered in traditional and gas-based microwave pyrolysis processes, producing a bio-oil that naturally partitions into a sugar-rich aqueous phase and a phenol-rich organic phase. Energy requirements are as low as 2 kJ/g for 50% volatilisation, comparable to microwave pyrolysis using inert gases. It is shown that the new concept works effectively with both microwave-transparent and microwave-absorbent solvents. The liquid media also acts to eliminate arcing and prevent carbonaceous residues from forming, phenomena which have so far proved challenging for the scale-up of microwave pyrolysis processes.